2012
DOI: 10.1021/jf204112f
|View full text |Cite
|
Sign up to set email alerts
|

Phlorotannins from Brown Algae (Fucus vesiculosus) Inhibited the Formation of Advanced Glycation Endproducts by Scavenging Reactive Carbonyls

Abstract: Accumulation of advanced glycation end products (AGEs) in vivo is associated with aging, diabetes, Alzheimer's disease, renal failure, etc. The objective of this study was to investigate the inhibitory effects of brown algae Fucus vesiculosus phlorotannins on the formation of AGEs. F. vesiculosus phlorotannins were extracted using 70% acetone. The resultant extract was fractionated into dichloromethane, ethyl acetate, butanol, and water fractions. The ethyl acetate fraction was further fractionated into four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 29 publications
4
49
1
1
Order By: Relevance
“…This result could explain that despite depletion of atRAL in primary cells treated with phloroglucinol, the chromene derivative was not detected, suggesting the formation of different adducts in the cellular context (dimeric chromene compounds or reversible adducts). To support this hypothesis, it has been shown that a molar excess of phloroglucinol can form various adducts with glyoxal and methylglyoxal [25].…”
Section: Discussionmentioning
confidence: 99%
“…This result could explain that despite depletion of atRAL in primary cells treated with phloroglucinol, the chromene derivative was not detected, suggesting the formation of different adducts in the cellular context (dimeric chromene compounds or reversible adducts). To support this hypothesis, it has been shown that a molar excess of phloroglucinol can form various adducts with glyoxal and methylglyoxal [25].…”
Section: Discussionmentioning
confidence: 99%
“…Considering MGO co-eluted with the mobile phase, this dicarbonyl was allowed to react with o-phenylenediamine to form stable 2-methylquinoxaline for reliable quantification by UHPLC [24,26]. Briefly, MGO (1 mM) was incubated with PBS (control), or test samples (1 mM) in PBS (100 mM, pH 7.4) at 37 • C and shaken at 70 rpm for 0-24 h, respectively.…”
Section: Mgo Scavenging Assaymentioning
confidence: 99%
“…This assay was adopted from the literatures with some modifications and used to evaluate inhibitory effects of compounds on protein glycation induced by MGO [24,26]. Briefly, HSA (10 mg/mL) was incubated with MGO (5 mM) in the absence or presence of test compounds (0.2, 0.5, 1 mM) in PBS (100 mM, pH 7.4) at 37 • C for 7 days.…”
Section: Hsa-mgo Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of phlorotannin oligomers, including fucophlorethol A, tetrafucol A and trifucodiphlorethol A, isolated from Fucus vesiculosus Linnaeus (obtained from Maine Seaweed Co. (Steuben, ME, USA)), was able to scavenge reactive carbonyls, inhibiting the formation of AGEs (Figure 4) [66]. …”
Section: Neuroprotective Compounds From Macroalgaementioning
confidence: 99%